Penerapan Sosialisasi Edukasi dan Informasi New Normal Menggunakan E-Poster Pada SDN 1 Sikui - Lili Rusdiana; Abraham Pamungkas Mara Putra; Hery Hermawan; Jamalul Insan; Novi Vebriyanti; Reffaldi Reffaldi (Jurnal Pengabdian Masyarakat - PIMAS, 2023)
E-posters as a substitute for posters are in digital form so that the distribution of posters can be done more widely and more easily without being limited by space and time, and can even spread to areas far from urban areas. SDN 1 SIKUI Muara Teweh City has minimal use of e-posters in the school environment, this occurs due to the lack of use of e-posters as a means that can provide education and information, especially about healthy living during a pandemic. In addition, the function of the poster is to convey information to more groups of people such as teachers, students, parents/guardians of students at SIKUI 1 Public Elementary School, Muara Teweh City, and can even reach the general public. In carrying out this community service, implementers use methods that are used online to distribute e-posters about implementing healthy living in schools. Six e-posters were made and distributed to SDN 1 SIKUI environment in Muara Teweh City. After this implementation, the e-posters could attract students' attention about the importance of maintaining health during a pandemic.